Reconstructing Holocene Glacier and Climate Fluctuations From Lake Sediments in Vårfluesjøen, Northern Spitsbergen - Røthe, Torgeir O.; Bakke, Jostein; Støren, Eivind W. N.; Bradley, Raymond S. (Frontiers in Earth Science, 2018)
A process-based understanding of lacustrine-deposited sediments in Arctic lakes is essential to set the present warming and hydroclimatic shift into perspective. From such a perspective, we can enhance our understanding of the natural climate variability in the Arctic. Here, we present work from the northern coast of Spitsbergen in which we unravel the sediment sequence from a distal glacier-fed lake, Vårfluesjøen. Utilizing recent methodological and technological developments, we base our interpretation on new tools that better visualize and characterize the sediments cores. High-resolution X-ray Computed Tomography (X-ray CT) is used to visualize the lake sediments and quantify the sand-sized particles found in the 210Pb- and radiocarbon-dated sediments, together with a multi-proxy approach including measurement of their physical, geochemical, and magnetic properties. Our findings suggest that Vårfluesjøen (6 m a.s.l.) was isolated from Woodfjorden at c. 10,200 ± 260 cal. yr. BP. During the early Holocene, the glaciers in the Vårfluesjøen catchment were considerably smaller than today or had even melted completely. At the start of the Neoglacial period (c. 3500 cal. yr. BP), we find increased glacier activity in the catchment of the lake. X-ray CT reveals an increased frequency of sand-sized particles from 3500 to 1750 cal. yr. BP, suggesting greater wintertime aeolian activity. Starting c. 2250 years ago, we find a progressive increase in snowmelt runoff in the Vårfluesjøen catchment, with peak runoff from 1000 to 750 cal. yr. BP. This coincides with a drop in sand-sized particles, hence less favorable environment for aeolian activity, and implying wetter conditions. During the last 2000 years, there is evidence for high glacier activity between c. 2000 to 900 and 750–350 cal. yr. BP. In between these time spans, less activity is recorded in the periods 1900–1800, 1000–800, and 350–150 cal. yr. BP.